ASUPAN TINGGI NATRIUM DAN BERAT BADAN LAHIR SEBAGAI FAKTOR RISIKO KEJADIAN HIPERTENSI OBESITAS PADA REMAJA AWAL - Fatta, Lutfiana Amirullah; Sulchan, Muhammad (Journal of Nutrition College, 2012)
Background: Obesity Hypertension does not only occur in adults or elderly, but also can occur on adolescents. Obesity Hypertension risk factors on adolescents as well as risk factors for obesity and hypertension. High-sodium intake and birth weight are two of the several risk factors for obesity hypertension. The purpose of this study was to determine magnitude of risk factors of high-sodium intake and birth weight on obesity hypertension occurance on early adolescence. Method: The study was carried out in SMP 3, SMP 30, SMP Kesatrian 2, and Madrasah Al-Khoiriyah. The design of this study is case-control with the amount of subjects are 72 consist of 36 cases and 36 controls. The subjects were selected that met the inclusion criteria. Data sodium intake is obtained by interview using Food Frequency Questionnaire last one month. Data on birth weight is obtained from interview with parents which supported by the record of KMS / KIA. Height measurements using microtoise, weight using digital scales, waist circumference using a tape measure, and blood pressure using a sphygmomanometer. Results: The prevalence of obesity hypertension is 7.5%. In this study, it is found that there is a significant correlation between high-sodium intake (p = 0.042; OR = 3.5) birth weight (p = 0.012; OR = 3.7) on obesity hypertension occurance on early adolescence. Conclusion: High-sodium intake and birth weight are risk factor of obesity hypertension on early adolescence. Major risk factors of high-sodium intake and birth weight are respectively 3.5 times and 3.7 times